Raising Barns. - Grier, David Alan (Computer (00189162), 2010)
The article reflects on the future of software engineering. It argues that software engineering education needs more experience than could be gained from traditional textbooks and classes. Professor Edsgar Dijkstra advocated a form of system development that he called structured programming based on practical activities.